Influence of Corrosion and Fatigue on the Bending Performances of Damaged Concrete Beams - Shiqin He; Zeyang Cao; Jiajun Ma; Shuai Zeng; Pengfei Li; Hui Wang (Advances in Civil Engineering)
The durability of in-service reinforced concrete bridges will be greatly reduced under the action of corrosion and the repeated load such as vehicles. In this paper, six reinforced concrete beams were cast and subjected to sustained load test for one year, and then, the alternating test of corrosion and fatigue load were carried out with the damaged concrete beams. The long-term deflection, fatigue lifetime, failure modes, and crack growth were investigated under different corrosion and fatigue working conditions. The fracture section of steel bars was scanned by electron microscopy at the end of fatigue test. The results indicate that the deflection of the beams will continue to increase under a long-term load. The chloride salt in the beam has little influence on the deflection performance, but will shorten the fatigue lifetime due to the corrosion of the steel bars. Moreover, the corrosion environment can accelerate the rusting of the beam bar and reduce the fatigue lifetime, the accumulation of deflection damage and crack damage, and other fatigue characteristics. The crack initiation-propagation-fracture stage of steel bars occurs in the process of fatigue.